PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA DESA SENDANG KECAMATAN WONOGIRI KABUPATEN WONOGIRI - Rahmawati, Dewi Aprilia; Suwardi; Winduro, Wirid (Solidaritas, 2024)
Community involvement in the development of the Sendang Piniri Tourism Village,located in Sendang Village, Wonogiri District, Wonogiri Regency, is an important aspectin efforts to achieve sustainable development. This research aims to analyze and describehow the community participates in the development of the tourist village. A qualitativeapproach was used in this research by referring to the theory of levels of communityparticipation put forward by Amstein (1969). According to the classification proposed byYadav (2018), there are four types of community participation, namely participation indecision making, implementation of activities, monitoring and evaluation, and utilizationof the results of tourism village development. Data was collected through observation, interviews and documentation, then analyzed using the stages of collection, reduction,presentation and drawing conclusions. The results show variations in communityparticipation patterns. Overall, community participation in the development of theSendang Pinilih Tourism Village shows a varied pattern, where several stages show agood level of participation. However, there is a need to increase participation in certainareas such as monitoring and evaluation.Keyword: community participation, tourism village development, Wonogiri.